Essential Dutch grammar - Stern, Henry R. (Dover books on language., 1984)
Based on the premise that systematic study of grammar is a shortcut to language learning, ESSENTIAL DUTCH GRAMMAR helps the language student acquire fluency by emphasizing the similarities between English and Dutch and by concentrating on essentials, such as spelling, word order, parts of speech, and other elements of grammar--all illustrated with easy-to-understand examples.